Leigos para o Desenvolvimento: Fundraising dynamic and donor loyalty of a NGO - Laureano, Raul M. S.; Nuno Santos; Martins, Sandrina; Pereira, Joana (VI International Congress of Teaching Cases Related to Public and Nonprofit Marketing, 2014)
The Leigos para o Desenvolvimento is a Non Governmental Organization for Development whose activity began in 1986 and has come to feel the need to boost the organization's marketing. However, in order to be able to apply the techniques of marketing to the tertiary sector, it is essential to know the behavior of donors, for different marketing actions may show different performances and different dynamics in fundraising. The objective of this study is to understand the dynamics of fundraising and donors, and thus support the decision making on future marketing actions, either online or offline. Throughout the study, there was verified a strong dependence of the donors that donate only once, so using the obtained knowledge that it is recommended that future marketing campaigns take into account the donor retention.